Mental health literacy: a systematic review of knowledge and beliefs about mental disorders in Malaysia - Munawar, Khadeeja; Mukhtar, Firdaus; Choudhry, Fahad Riaz; Oon Ng, Alvin Lai (John Wiley & Sons, 2021)
Background Mental health problems in Malaysia are on a rise. This study aimed at performing a systematic review of mental health literacy (MHL) in Malaysia.